UPAYA MENINGKATKAN KETERAMPILAN BERBICARA MELALUI METODE PEMBELAJARAN LIHAT UCAP DI KELAS I SDN 005 KOTO SENTAJO KECAMATAN SENTAJO RAYA - Nurhasnah Nurhasnah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
Learning Indonesian is directed to improve the ability of learners in communicating orally and in writing. Theability to communicate well and correctly is in accordance with the context of time, purpose and atmospherewhen communication is held. This research is a classroom action research by taking data on daily test I anddaily test II with assessment of three aspects, namely speaking intonation, pronunciation, and voice clarity.From the research result, the use of look and speech method was able to improve the speaking skill of children inclass I SDN 005 Koto Sentajo with very high category on daily test I with the number of students two peopleincreased to five people. In the high category of the number of eight students in the daily test II increased in thedaily test II with a total of seven students, while in the ample category in repeat I with the number of studentsfour people increased to two students in Repeat II. With an overview of the research data, the use of the methodcan be seen as effective in improving students' speaking skills in primary schools.